2014
DOI: 10.1007/s00404-014-3563-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of uterine artery Doppler and NT-proBNP levels in the second trimester to predict preeclampsia

Abstract: Bilateral notch together with abnormal PI measurements in the uterine artery Doppler screening during the second trimester was associated with poor perinatal outcomes. Such an association was not significant in the NT-proBNP measurements. Larger trials focused on late-onset preeclampsia are needed to draw definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…The first trimester UAD has elusive or limited diagnostic accuracy in predicting preeclampsia and FGR [3,11,12,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] IV 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first trimester UAD has elusive or limited diagnostic accuracy in predicting preeclampsia and FGR [3,11,12,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] IV 9…”
Section: Methodsmentioning
confidence: 99%
“…(1) the first trimester UAD indices are highly predictive of both preeclampsia and FGR [5,7,9,10,; (2) the first trimester UAD is highly predictive of preeclampsia and fairly predictive or not predictive of the FGR [1,2,8,; (3) the first trimester UAD has elusive or limited diagnostic accuracy in preeclampsia and FGR [3,11,12,[57][58][59][60][61][62][63][64][65][66][67][68][69][70]; and (4) the first trimester UAD indices are not predictive of preeclampsia or FGR [6,[71][72][73][74][75][76][77][78].…”
Section: Problem Definitionmentioning
confidence: 99%
“…Otra investigación en pacientes con quemaduras severas demostró que el aumento en las concentraciones de PNC y la disminución de la proteinuria, reflejo de la disminución del daño capilar, están asociadas con un menor número de complicaciones (26) . Al igual que esta investigación, un estudio previo no fue capaz de obtener datos sobre la correlación entre los péptidos natriuréticos y los valores de plaquetas, fosfatasa alcalina y proteinuria (27) .…”
Section: Resultsunclassified
“…Studies have reported elevated levels of NT-pro BNP in established pre-eclampsia with or without ventricular failure [ 14 , 16 , 37 ], but the benefit of using NT-pro BNP for predicting pre-eclampsia is uncertain [ 38 , 39 ]. A recent study reported a better predictive value for pre-eclampsia when adding NT-pro BNP to the existing biomarkers (soluble FMS-like tyrosine kinase 1 and placental growth factor) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%